Quality of maternal obstetric and neonatal care in low-income countries: development of a composite index - Wilhelm, Danielle J.; Lohmann, Julia; De Allegri, Manuela; Chinkhumba, Jobiba; Muula, Adamson S.; Brenner, Stephan (BMC medical research methodology, 2019)
In low-income countries, studies demonstrate greater access and utilization of maternal and neonatal health services, yet mortality rates remain high with poor quality increasingly scrutinized as a potential point of failure in achieving expected goals. Comprehensive measures reflecting the multi-dimensional nature of quality of care could prove useful to quality improvement. However, existing tools often lack a systematic approach reflecting all aspects of quality considered relevant to maternal and newborn care. We aim to address this gap by illustrating the development of a composite index using a step-wise approach to evaluate the quality of maternal obstetric and neonatal healthcare in low-income countries.